Instagram as an Information Media for Feminism Education in the Frame of Husserls' Phenomenology - Ida Ayu Shinta Indah Permata; Munadhil Abdul Muqsith; Fitria Ayuningtyas (Syntax Corporation Indonesia, 2023)
The phenomenon of using social media as a medium to meet the information and education needs of society is the result of the rapid development of the internet. Now people's needs are easily met, because various things are included in it. This can be analyzed based on the phenomenon of Instagram accounts as information on feminism education in the Instagram account @perempuanbercerita. The purpose of writing this research article is that the many cases against women make Instagram an information medium capable of providing feminist education to followers, using qualitative research methods with observation, note-taking and descriptive analysis techniques, with the phenomenological study approach of Edmund Husserls. The research subject is the flow of feminist educational information from the Instagram account @perempuanbercerita to followers of the Instagram account @perempuanbercerita. The use of social media Instagram as an educational medium, as well as empowering women, produces responses in the form of information, emotions and actions in accessing @perempuanbercerita posts as well as conscious experiences in cognitive and perceptual aspects in line with the development of the same meaning related to feminist values.